Treatment Efforts for PTSD Patients at the RSJ Nurrohman Kasemen Serang Banten Foundation - Sari, Fitri Puspita; Nadirah, Yahdinil Firda (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research was conducted at the RSJ Nurrohman Kesemen Foundation, the researcher took this place because the researcher only focused on subjects who were included in ODGJ (People with Mental Disorders) who had problems with trauma disorders or Post Traumatic Stress Disorder. This subject experiences disturbances in his memory power, he sometimes forgets himself, feels afraid of people around him, is often alone, has difficulty sleeping and likes to engage in irregular behavior and words. This research aims to enable RSJ to increase insight into the treatment of PTSD patients.